Pillars of Democracy in Pakistan: Judiciary and Media: Exploring the Nexus between State Actors, Terrorism, and India-Pakistan Relations in Pakistan (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Also, it is important to understand how during the initial years of state-formation, certain circumstances and domestic players shaped the future of Pakistan with democracy strangled by the ‘men on the horseback’ holding onto the reins of power. Thus, it becomes important to study Pakistan as a state and the role played by different state actors (as well as non-state actors) in shaping the country mired in serious structural problems. It would help in understanding the role of each actor in the circumstances that created conducive environment for terrorism to breed. Also, how policy making is influenced in Pakistan thereby affecting its relationship with India. This would ultimately lead us to understanding why Pakistan sponsors terrorism into India, creating internal security problems for India.